KERJASAMA PERDAGANGAN INDONESIA-JEPANG DI SEKTOR PERIKANAN DALAM INDONESIA-JAPAN ECONOMY PATNERSHIP AGREEMENT (IJEPA) PERIODE 2014-2017 - Dita Tiara Ayu, - (2018)
This research was conducted to present research that discusses the "Indonesian- Japanese trade cooperation in fishery sector in indonesia-japan economy patnership agreement period 2014-2017" as we know cooperation is done to increase the income of the two countries. Formulation of the problem in this research question "why is there a decline in the export of fishery 2014-2017 period of Indonesia". To answer the questions of research, the author uses the framework of the free trade theory, the theory of national interest and the concept of the EPA. The author uses a qualitative method where the author seeks to provide an explanation regarding the cooperation of Indonesia and Japan performed with IJEPA in the fishery as well as primary or secondary data collecting through interviews and data analysis . In cooperation between Indonesia with IJEPA there are several "Barriers" that make this cooperation is judged not yet profitable for Indonesia